The Effect of Cost Control and Budget Planning on MSME Cost Efficiency: The Mediating Role of Accounting Information Quality and Business Complexity - Mahyudin, Mahyudin; Nasir, Miftah Faridh (Journal Of Accounting Management Business And International Research, 2025)
This study aims to examine the effect of cost control and budget planning on cost efficiency among Micro, Small, and Medium Enterprises (MSMEs), with accounting information quality and business complexity as intervening variables. A quantitative research approach was employed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The research population consisted of 488 MSMEs operating in Medan City, and a sample of 220 respondents was determined using the Slovin formula. Data were collected through questionnaires and analyzed using SmartPLS 4.0. The results indicate that both cost control and budget planning have a positive and significant direct effect on cost efficiency. Furthermore, cost control and budget planning significantly influence the quality of accounting information and business complexity. However, accounting information quality was found to have no significant effect on cost efficiency, while business complexity positively and significantly affected cost efficiency. Mediation analysis revealed that business complexity mediates the relationship between cost control and budget planning with cost efficiency. Meanwhile, accounting information quality only mediates the relationship between budget planning and cost efficiency but does not mediate the effect of cost control on cost efficiency. These findings highlight the critical role of budget planning and cost control, integrated with business complexity management, in enhancing cost efficiency for MSMEs. The study provides practical implications for policymakers and practitioners, particularly the need for managerial training and financial mentoring to strengthen budgeting practices, improve accounting systems, and implement effective cost control strategies to ensure business sustainability and competitiveness.